Light diffraction through a feather - Pérez García, Hugo;; García Molina, Rafael;; Abril, Isabel (Revista Eureka sobre Enseñanza y Divulgación de las Ciencias, 2012)
We have used a feather to study light diffraction, in a qualitative as well as in a quantitative manner. Experimental measurement of the separation between the bright spots obtained with a laser pointer allowed the determination of the space between feather's barbs and barbules. The results we have obtained agree satisfactorily with those corresponding to a typical feather. Due to the kind of materials, the related concepts and the experimental results, this activity becomes an excellent didactic resource suitable for studying diffraction, both in introductory undergraduate as well as in secondary school physics courses.